CLINICAL OUTCOME IN BILATERAL STURGE-WEBER SYNDROME - Alkonyi, Bálint (2011)
Approximately 15% of patients with Sturge-Weber syndrome have bilateral intracranial involvement and the prognosis of these patients is believed to be particularly unfavorable. We reviewed the clinical and neuroimaging features of patients with Sturge-Weber syndrome and bilateral intracranial involvement. Seizure variables, presence of hemiparesis and degree of developmental impairment at last follow-up were compared to imaging abnormalities. Out of 110 Sturge-Weber syndrome patients studied, 14 had bilateral brain involvement, which always showed an asymmetric pattern on glucose metabolism positron emission tomography. Although most patients had frequent seizures initially, associated with frontal hypometabolism on positron emission tomography, six patients (43%) had achieved good seizure-control during follow-up. Bilateral frontal hypometabolism was associated with severe developmental impairment; two children with bitemporal hypometabolism showed autistic features. Hemiparesis was associated with superior frontal (motor cortex) hypometabolism. Three patients had resective surgery, resulting in improved seizure control and/or developmental outcome. The severity of neurological complications and clinical course depend highly on the extent of cortical dysfunction in bilateral Sturge-Weber syndrome; bilateral frontal and temporal hypometabolism is associated with poor developmental outcome. Nevertheless, good seizure control and only mild/moderate developmental impairment can be achieved in about half of bilateral Sturge-Weber syndrome patients, with or without resective surgery.